Carbon cloth loaded Ni perylene-based composite material electrode and application of preparation method thereof in electro-catalytic nitrate reduction
By using carbon cloth-supported perylene-based composite electrodes for electrocatalytic nitrate reduction, the problems of low efficiency and high cost of traditional nitrate removal methods are solved, and efficient and economical nitrate removal effect is achieved.
Patent Information
- Application Number
- CN202510037610.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
Traditional nitrate removal methods have problems such as low efficiency, high cost and complex operation, and it is difficult to effectively remove nitrate pollution in water bodies.
A perylene-based composite electrode with carbon cloth supported Ni is used to achieve efficient removal of nitrate by electrocatalyzing nitrate reduction. This electrode is prepared by simple and easy-to-get raw materials and simple hydrothermal methods, with stable structure and high catalytic efficiency.
At -1.2V v.s.RHE, the Faraday efficiency was achieved at 31.49% and the ammonia nitrogen yield of 357.70 mmol h-1g-1 was achieved, which significantly improved the efficiency of nitrate reduction.
Smart Images

Figure CN119824474A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysis, and in particular relates to a carbon cloth-loaded Ni perylene-based composite material electrode and a preparation method thereof, and application thereof in electrocatalytic nitrate reduction. Background Art
[0002] With the acceleration of industrialization, water pollution is becoming increasingly serious, among which nitrate pollution has become one of the environmental problems that need to be solved urgently worldwide. Nitrates not only have a serious impact on aquatic ecosystems, but also pose a threat to human health. Although traditional nitrate removal methods, such as physical, chemical and biological methods, can reduce the nitrate concentration in water to a certain extent, they often have disadvantages such as low efficiency, high cost and complex operation. Therefore, it is particularly important to develop efficient and economical nitrate removal technology.
[0003] In recent years, electrochemical reduction technology has gradually become a research hotspot due to its simple operation, mild reaction conditions and environmentally friendly characteristics. Electrocatalytic nitric acid reduction of ammonia (NRA) has been widely studied as an eco-friendly technology with the potential for pollution removal and resource recycling.
[0004] Nickel (Ni), as a common transition metal, has attracted widespread attention due to its good catalytic activity and relatively low cost. Nickel-based catalysts have shown excellent performance in a variety of electrochemical reactions, especially in nitrogen reduction reactions. Combining perylene compounds with nickel to form perylene-based composite materials can not only give full play to the catalytic activity of nickel, but also utilize the excellent pore structure of perylene compounds to further improve the overall performance of the electrode.
[0005] In summary, the development of a new type of carbon cloth-loaded Ni-perylene-based composite electrode not only provides an efficient solution for electrochemical nitrate reduction, but also provides a new idea for water pollution control. Through in-depth research on this electrode, it is expected to achieve efficient removal of nitrates in water and make a positive contribution to environmental protection. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a carbon cloth-loaded Ni perylene-based composite material electrode with stable structure, simple preparation method, high catalytic efficiency and good selectivity, and its application in electrocatalytic nitrate reduction.
[0007] The technical solution adopted by the present invention is:
[0008] A carbon cloth loaded Ni perylene-based composite material electrode is provided, wherein Ni is used as a central metal atom and the perylene-based composite material in a dispersion liquid is used as a matrix, which is loaded onto the carbon cloth to prepare an electrode.
[0009] The method for preparing the above-mentioned carbon cloth-loaded Ni perylene-based composite material electrode comprises the following steps:
[0010] 1) Pretreatment of carbon cloth: Cut a rectangular carbon cloth into 1 cm × 2 cm size and soak it in acetone, anhydrous ethanol, concentrated nitric acid, anhydrous ethanol, and acetone in turn, ultrasonically treat for 30 min each time, wash it with deionized water several times, and dry it in a vacuum drying oven at 60 ° C for 48 hours;
[0011] 2) Preparation of carbon cloth-loaded Ni perylene-based composite material electrode: The Ni perylene-based composite material is mixed with acetylene black, naphthol film solution, isopropyl alcohol and ultrapure water and dispersed uniformly by ultrasonication to obtain a mixed ink; the mixed ink is ultrasonicated for 60 minutes, and the mixed ink is dripped on the carbon cloth with a 1 mL syringe, 8-10 drops are added, and the carbon cloth-loaded Ni perylene-based composite material electrode is obtained after drying.
[0012] Furthermore, in the above preparation method, the amount of the Ni perylene-based composite material is 4 mg, the amount of acetylene black is 1 mg, the amount of naphthol film solution is 30 μL, the amount of isopropanol is 500 μL, and the amount of ultrapure water is 200 μL.
[0013] Furthermore, the above-mentioned preparation method, the preparation method of the Ni perylene-based composite material comprises the following steps:
[0014] 1) dissolving perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) and imidazole in DMF to obtain a PTCDA solution, dissolving 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (TAPT) in DMF to obtain a TAPT solution, then slowly dropping the TAPT solution into the PTCDA solution, mixing evenly by ultrasonication, and continuously refluxing for 48 hours under stirring at 180° C., collecting the precipitate by filtration, repeatedly washing with DMF, and drying to obtain a perylene-based material;
[0015] 2) Nickel nitrate hexahydrate, thiourea and perylene-based materials are dissolved in THF, ultrasonically mixed and then transferred to a reactor for reaction, the precipitate is collected by centrifugation, washed with ethanol for multiple times, and dried to obtain a Ni-loaded perylene-based composite material.
[0016] Furthermore, in the preparation method of the above-mentioned Ni perylene-based composite material, in step 1), 0.2354 g of PTCDA and 15 g of imidazole are dissolved in 17 mL of DMF, and 0.1417 g of TAPT is dissolved in 3 mL of DMF.
[0017] Furthermore, in the preparation method of the above-mentioned Ni-perylene-based composite material, in step 2), 0.2908 g of nickel nitrate hexahydrate, 0.07612 g of thiourea and 4.16838 g of perylene-based material are dissolved in 30 mL of THF.
[0018] Furthermore, in the above-mentioned method for preparing the perylene-based composite material of Ni, in step 2), the reaction is carried out at 160° C. for 24 hours.
[0019] Furthermore, in the above-mentioned method for preparing the perylene-based composite material of Ni, in step 1) and step 2), the drying condition is: vacuum drying at 60° C. for 48 hours.
[0020] The above-mentioned carbon cloth-loaded Ni perylene-based composite material electrode is used in electrocatalytic nitrate reduction.
[0021] Furthermore, the above application method is as follows: a carbon cloth-loaded Ni perylene-based composite material electrode is used as a working electrode, a counter electrode is a platinum sheet electrode, a reference electrode is an Ag / AgCl electrode, 35 mL of each 0.1 M KNO3 solution and 1 M KOH solution are used as the cathode electrolyte, the anolyte is the same as the cathode electrolyte, electrolysis is performed at a potential of -0.7 to -1.3 V vsRHE for 1 hour, and the cathode electrolyte product is collected.
[0022] The beneficial effects of the present invention are:
[0023] 1. The present invention uses simple and readily available raw materials to synthesize perylene-based composite materials through a simple hydrothermal method. The present invention uses simple and readily available raw materials to synthesize catalyst powder through a simple solvent thermal strategy, and prepares it into ink to load it on carbon cloth. The obtained material has a stable structure and simple synthesis operation.
[0024] 2. The catalyst synthesized by the present invention is used for electrocatalytic nitrate reduction, and achieves a Faradaic efficiency of 31.49% at -1.2 V vs RHE, and a maximum of 357.70 mmol h -1 g -1 Ammonia nitrogen yield.
[0025] 3. The raw materials used in the method of the present invention are simple and easy to obtain, the operation steps are simple and feasible, the material exhibits good electrocatalytic performance, and has good application prospects in the field of electrocatalytic reduction of nitrate to produce ammonia. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 FT-IR spectra of the perylene-based composite material prepared in Example 1 and two raw materials.
[0027] Figure 2 1 is the XRD powder diffraction pattern of the Ni-loaded perylene-based composite material prepared in Example 1 and two raw materials.
[0028] Figure 3 It is the solid ultraviolet spectrum of the Ni-loaded perylene-based composite material prepared in Example 1 and two raw materials.
[0029] Figure 4 It is a UV-vis absorption spectrum of the ammonia nitrogen content in the electrolyte detected by the indophenol blue method in Example 2.
[0030] Figure 5 This is the standard curve for detecting the ammonia nitrogen content in the electrolyte by the indophenol blue method in Example 2.
[0031] Figure 6 This is a graph of ammonia nitrogen yield and Faraday efficiency of the perylene-based composite electrode material loaded with Ni on carbon cloth in Example 2. DETAILED DESCRIPTION
[0032] Example 1 Preparation of carbon cloth loaded Ni perylene-based composite electrode
[0033] (I) The preparation method is as follows:
[0034] 1) Pretreatment of carbon cloth: A rectangular carbon cloth cut into a size of 1 cm × 2 cm was soaked in acetone, anhydrous ethanol, concentrated nitric acid, anhydrous ethanol, and acetone in turn, each time with ultrasound for 30 min, and washed several times with deionized water and then dried in a 60°C vacuum drying oven for 48 hours.
[0035] 2) Preparation of Ni-based perylene composite material: Accurately weigh 0.2354g PTCDA and 15g imidazole and dissolve them in 17mL DMF, accurately weigh 0.1417g TAPT and dissolve it in 3mL DMF, then slowly add the TAPT solution to the PTCDA solution, mix it evenly by ultrasonication for 20min, continue to reflux for 48 hours under stirring at 180℃, collect the precipitate by filtration, wash it repeatedly with DMF, vacuum dry it at 60℃ for 48 hours, grind it into powder, and obtain the perylene-based material. Dissolve 0.2908g nickel nitrate hexahydrate, 0.07612g thiourea and 4.16838g perylene-based material in 30mL THF, mix it evenly by ultrasonication for 20min, transfer it to a reactor and react it at 160℃ for 24h. After high temperature reaction, cool it to room temperature, collect the precipitate by centrifugation, wash it with ethanol several times, vacuum dry it at 60℃ for 48 hours, grind it into powder, and obtain the perylene-based composite material loaded with Ni.
[0036] 3) Preparation of carbon cloth-supported Ni perylene-based composite electrode: 4 mg Ni perylene-based composite powder, 1 mg acetylene black, 30 μL naphthol film solution, 500 μL isopropanol, 200 μL ultrapure water, mixed and dispersed evenly by ultrasonic for 30 min to obtain a mixed ink. Use a 1 mL syringe to drop the mixed ink on the carbon cloth, add 8-10 drops, dry and weigh, and calculate the catalyst loading according to the mass difference of the carbon cloth before and after.
[0037] (II) Test results
[0038] Figure 1is the FTIR spectrum of the perylene-based composite material powder prepared in Example 1. Figure 1 It can be seen that the perylene-based composite powder has a -1 The carbon-nitrogen bond stretching vibration peak at 1598 cm -1 The carbonyl asymmetric stretching vibration peak appears from the ligand PTCDA molecule, proving that PTCDA participates in the reaction. -1 No amino peak appeared at , indicating that the material was successfully synthesized and the reaction proceeded according to the experimental design. Figure 2 The XRD spectrum of the Ni perylene-based composite material prepared in Example 1 is compared with the spectra of the raw materials TAPT and PTCDA. In the newly synthesized composite material powder, the peak of the PTCDA raw material disappears, proving the generation of new substances.
[0039] Example 2 Application of carbon cloth loaded Ni perylene-based composite electrode in electrocatalytic nitrate reduction
[0040] Test method: The carbon cloth loaded Ni perylene-based composite material electrode prepared in Example 1 was used as the working electrode.
[0041] The electrolytic cell used in the experiment is an H-type electrolytic cell, the Nafion117 membrane is a proton exchange membrane, the electrode prepared in Example 1 is placed on the cathode electrode clip as the working electrode, the Ag / AgCl electrode is the reference electrode, the platinum electrode is the counter electrode, the cathode electrolyte is 35mL 0.1M KNO3 solution and 35mL 1M KOH solution, and the anolyte is 35mL 0.1M KNO3 solution and 35mL1M KOH solution. The experimental potential is set to -0.7~-1.3V vsRHE, the IT test time is 1h, the cathode electrolyte product is collected, and the ammonia nitrogen content in the electrolyte is detected using the indophenol blue method.
[0042] Figure 3 The solid UV spectrum of the Ni perylene-based composite material powder prepared in Example 1 is compared with the spectra of the raw materials TAPT and PTCDA. In the newly synthesized composite catalyst powder, no obvious peaks in the raw materials appear, proving the synthesis of the new material.
[0043] Figure 4 , Figure 5 The UV-vis absorption spectrum and standard curve of the indophenol blue method for detecting the ammonia nitrogen content and Faraday efficiency in the electrolyte are shown in the figure. The experiment sets five standard curve concentration ranges of 0.0, 0.2, 0.8, 1.0, and 1.2 μg mL -1 , the R of the standard curve was experimentally measured 2 It reaches 0.99955, with high reliability, and can be used as an external standard curve. Figure 6The results show that the composite electrode achieves a maximum Faradaic efficiency of 31.49% at -1.2 V vs RHE and a maximum capacity of 357.70 mmol / h -1 g -1 Ammonia nitrogen yield.
[0044] In summary, the Ni-loaded perylene-based composite material electrode of the present invention has high Faradaic efficiency and ammonia nitrogen yield, and at the same time has good electrocatalytic stability. Therefore, this carbon cloth-loaded Ni-loaded perylene-based composite material electrode has a relatively ideal development prospect in the field of electrocatalytic nitrate reduction.
[0045] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any person skilled in the art can use the above disclosed technical contents to change or modify them into equivalent embodiments with equivalent changes. Any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A carbon cloth loaded Ni perylene-based composite material electrode, characterized in that: Taking Ni as the central metal atom and the perylene-based composite material in the dispersion as the matrix, it is loaded on the carbon cloth to prepare the electrode.
2. The method for preparing a carbon cloth-supported Ni perylene-based composite material electrode according to claim 1, characterized in that: The steps include: 1) Pretreatment of carbon cloth: Cut a rectangular carbon cloth into 1 cm × 2 cm size and soak it in acetone, anhydrous ethanol, concentrated nitric acid, anhydrous ethanol, and acetone in turn, ultrasonically treat for 30 min each time, wash it with deionized water several times, and dry it in a vacuum drying oven at 60 ° C for 48 hours; 2) Preparation of carbon cloth-loaded Ni perylene-based composite material electrode: The Ni perylene-based composite material is mixed with acetylene black, naphthol film solution, isopropyl alcohol and ultrapure water and dispersed uniformly by ultrasonication to obtain a mixed ink; the mixed ink is ultrasonicated for 60 minutes, and the mixed ink is dripped on the carbon cloth with a 1 mL syringe, 8-10 drops are added, and the carbon cloth-loaded Ni perylene-based composite material electrode is obtained after drying.
3. The preparation method according to claim 2, characterized in that: The amount of the Ni perylene-based composite material used is 4 mg, the amount of acetylene black used is 1 mg, the amount of naphthol membrane solution used is 30 μL, the amount of isopropanol used is 500 μL, and the amount of ultrapure water used is 200 μL.
4. The preparation method according to claim 2, characterized in that: The preparation method of the Ni perylene-based composite material comprises the following steps: 1) PTCDA and imidazole are dissolved in DMF to obtain a PTCDA solution, TAPT is dissolved in DMF to obtain a TAPT solution, and then the TAPT solution is slowly added dropwise to the PTCDA solution, ultrasonically mixed, and refluxed for 48 hours under stirring at 180° C., and the precipitate is collected by filtration, repeatedly washed with DMF, and dried to obtain a perylene-based material; 2) Nickel nitrate hexahydrate, thiourea and perylene-based materials are dissolved in THF, ultrasonically mixed and then transferred to a reactor for reaction, the precipitate is collected by centrifugation, washed with ethanol for multiple times, and dried to obtain a Ni-loaded perylene-based composite material.
5. The preparation method according to claim 4, characterized in that: In step 1), 0.2354 g of PTCDA and 15 g of imidazole were dissolved in 17 mL of DMF, and 0.1417 g of TAPT was dissolved in 3 mL of DMF.
6. The preparation method according to claim 4, characterized in that: In step 2), 0.2908 g of nickel nitrate hexahydrate, 0.07612 g of thiourea and 4.16838 g of perylene-based material were dissolved in 30 mL of THF.
7. The preparation method according to claim 4, characterized in that: In step 2), the reaction is carried out at 160° C. for 24 hours.
8. The preparation method according to claim 4, characterized in that: In step 1) and step 2), the drying condition is: vacuum drying at 60° C. for 48 hours.
9. Use of the carbon cloth-supported Ni perylene-based composite material electrode according to claim 1 in electrocatalytic nitrate reduction.
10. The use according to claim 9, characterized in that: The method is as follows: a carbon cloth-loaded Ni perylene-based composite material electrode is used as a working electrode, a counter electrode is a platinum sheet electrode, a reference electrode is an Ag / AgCl electrode, 35 mL each of a 0.1M KNO3 solution and a 1M KOH solution are used as the cathode electrolyte, the anolyte is the same as the cathode electrolyte, and electrolysis is performed at a potential of -0.7 to -1.3 V v.s. RHE for 1 h, and the cathode electrolyte product is collected.
Citation Information
Patent Citations
Method for producing amino-functional aromatic compounds
CN108138340A
Preparation method and application of single-atom copper material
CN111360279A
Method for synthesizing ammonia by electrocatalytic reduction of nitrate
CN116377454A
Perylene-based composite material, preparation method thereof and application of perylene-based composite material in electro-catalytic urea oxidation
CN117070995A
Cited By
Preparation method and application of a self-supporting ni-based catalyst
CN122629554A